Developing a value-based pencak silat training model for life skills formation: A sport for development and peace perspective - Hadiana, Oman; Firmana, Iif; Manan, Nanan Abdul; Falah, Irfan Fajrul; Fitriyani, Yani (UIR Press, 2025)
Background: Pencak silat, traditionally rooted in moral and spiritual education, has shifted toward a performance-driven orientation emphasizing medals and financial rewards. This transformation has contributed to concerns over youth moral decline, including reduced empathy and growing individualism. However, despite increasing attention to the role of sport in fostering life skills, little research has developed structured, value-based training models in pencak silat that intentionally incorporate Sport for Development and Peace (SDP) principles. Research Objectives: This study aimed to develop a Tapak Suci pencak silat training model from a Sport for Development and Peace (SDP) perspective, grounded in value-based education to foster athletes’ life skills. Methods: Employing the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model, 56 adolescent athletes were recruited and randomly assigned to experimental (n = 28) and control (n = 28) groups. Data were collected through observation, interviews, and questionnaires, while model validity was assessed by five experts and five practitioners. Findings/Results: The developed training model demonstrated strong validity (CVR = 0.99), practicality across small-scale (76%), medium-scale (80%), and field trials (81%), and significant effectiveness. Independent t-test analysis revealed higher life skills scores in the experimental group (M = 146.36) compared to the control group (M = 125.79, p < 0.05). Conclusion: The findings highlight that a value-based pencak silat training model effectively enhances athletes’ life skills, particularly in emotional regulation, problem-solving, leadership, and respect. Further research is recommended to extend the application of value-based approaches to other martial arts and diverse training contexts.